1996
DOI: 10.1001/archneur.1996.00550050066025
|View full text |Cite
|
Sign up to set email alerts
|

Gender Comparisons of Cognitive Performances Among Vascular Dementia, Alzheimer Disease, and Older Adults Without Dementia

Abstract: Findings support the existence of a semantic memory deficit for women with AD and suggest that a similar deficit may exist among women with VD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
24
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 32 publications
6
24
2
Order By: Relevance
“…Recent studies suggest that female AD patients show greater deficits on verbal fluency, naming and recall of words [10,18,19,33]. However, these studies are not comparable to the present study, as much more severely affected patients were investigated.…”
Section: ■ Patients With Adcontrasting
confidence: 96%
See 2 more Smart Citations
“…Recent studies suggest that female AD patients show greater deficits on verbal fluency, naming and recall of words [10,18,19,33]. However, these studies are not comparable to the present study, as much more severely affected patients were investigated.…”
Section: ■ Patients With Adcontrasting
confidence: 96%
“…Several investigators provided evidence that demented men seem to retain verbal skills better than women [10]. Recent studies suggest that female AD patients show greater deficits on verbal fluency, naming and recall of words [10,18,19,33].…”
Section: ■ Patients With Admentioning
confidence: 99%
See 1 more Smart Citation
“…Armstrong and Walker (1994) found that on formal verbal ability and verbal memory tests, males and females produced similar results. While finding gender differences in the performance of demented elderly participants, Buckwalter et al (1996) report no significant differences in non-demented elderly on a global screening measure, tests of visuospatial organization and construction, and a semantic naming task. Corey-Bloom et al (1996) also found there to be no gender differences in performance on their battery (global screening, verbal and visual memory tasks, category fluency, and maintaining cognitive set).…”
mentioning
confidence: 68%
“…Given the strong effect of age on the incidence of dementia, women's greater susceptibility to dementia is due in large part to their greater longevity. Nevertheless, after correction for age, women remain more frequently affected by dementia than men [2]. Moreover, gender differences are not only found in neuropathology but also in cerebral glucose metabolism and blood flow [12,15].…”
Section: Introductionmentioning
confidence: 99%